SCARB1 rs5888 is associated with the risk of age-related macular degeneration susceptibility and an impaired macular area. (4th May 2017) - Stanislovaitiene, Daiva; Zaliuniene, Dalia; Krisciukaitis, Algimantas; Petrolis, Robertas; Smalinskiene, Alina; Lesauskaite, Vita; Tamosiunas, Abdonas; Lesauskaite, Vaiva
ABSTRACT: Background : Age-related macular degeneration (ARMD), a progressive retinal disease, is responsible for an impaired central vision in about 180 million people worldwide. Current options for ARMD prevention and treatment are limited due to an incomplete understanding of disease etiopathogenesis. We aimed to test the hypothesis that the single nucleotide polymorphism rs5888 of SCARB1 gene reflecting lipid and antioxidant micronutrient metabolism pathways is associated with ARMD susceptibility and to evaluate if there is any relation between SCARB1 rs5888 and the macular lesion area. Materials and methods : The prospective case-control study included patients with ARMD ( n = 215) and the reference group ( n = 238) drawn from a random sample of the Lithuanian population ( n = 1436). The genotyping test of SCARB1 rs5888 was carried out using the real-time polymerase chain reaction method. Results : Regression analysis adjusted by gender and age demonstrated that SCARB1 rs5888 TT genotype significantly decreased the odds for ARMD development (OR: 0.61, 95%; CI: 0.380–0.981, p = 0.04). A smoking habit and leading an outdoor life are associated with larger macular lesion areas in ARMD patients (0.54 (0.00–39.06) vs. 3.09 (0.02–19.30) and 0.27 (0.00–34.57) vs. 0.75 (0.00–39.06), respectively). In late stage ARMD subjects with CT genotype, the macular lesion area was larger than in TT carriers (7.64 (0.49–39.06) mm 2 vs. 5.02 (0.03–37.06) mm 2, p = 0.006). Conclusions: SCARB1 rs5888 and environmental oxidative stress have a prominent role in ARMD susceptibility, early ARMD progression to advanced stage disease and even in the outcome of the disease—an area of macular lesion.